Revealing the dominant chemistry for oxygen reduction reaction on small oxide nanoparticles - Zhou, Ye (2020)
The bulk chemistry has been successfully used as a descriptor for oxygen reduction reaction (ORR) activities of various metal oxides. However, as the size of oxides becomes small, the bulk chemistry may not be sufficient to describe the activities. Here, we report a systematic study on Mn-substituted ferrite MnxFe3–xO4 (x = 0.5–2.5) nanoparticles and the roles of surface Mn in determining their ORR activities. Gradual Mn substitution induced changes in Mn valence and crystal structure. However, there is no remarkable correlation that can be found between their bulk chemistry and ORR activities. Instead, the surface Mn density and valency were found to play dominant roles in determining the ORR. This work shows that, at a small particle size, the bulk chemistry of oxides may not be the descriptor for their electrochemical properties. Due to the significantly high surface/bulk ratio, the surface chemistry has to be carefully characterized to interpret the activities of oxide nanoparticles.